The impact of type 2 diabetes and obesity on the long‐term outcomes of more than 85 000 liver transplant recipients in the US. Issue 6 (16th July 2014) - Younossi, Z. M.; Stepanova, M.; Saab, S.; Kalwaney, S.; Clement, S.; Henry, L.; Frost, S.; Hunt, S.
Summary Background Type 2 diabetes is known to negatively impact the outcome of chronic liver disease. Aim To evaluate the impact of diabetes on the outcomes of liver transplants (LT). Methods Study cohort included adults (>18 years) who received LT in the US between 1994 and 2013 (The Scientific Registry of Transplant Recipients). Pre‐ and post‐transplant diabetes was recorded in patients with mortality follow‐up. Results We included 85 194 liver transplant recipients. Of those, 11.2% had history of pre‐transplant diabetes. The most common indications for liver transplant were hepatitis C (36.4%), alcohol‐related liver disease (20.6%), primary liver malignancy of unspecified aetiology (14.7%), cryptogenic cirrhosis (8.0%), hepatitis B (4.6%) and non‐alcoholic steatohepatitis (3.9%). A total of 96.5% transplants were from deceased donors, and 7.9% donors had history of diabetes. During an average 6.5 years of follow‐up, 31.3% recipients died and 8.8% had a graft failure. In multivariate survival analysis [at least 5 years of cohort follow‐up (N = 35 870)], after adjustment for age, ethnicity, insurance type, history of chronic diseases, HCV infection and noncompliance, independent predictors of recipient mortality included the presence of pre‐transplant diabetes [adjusted hazard ratio (95%CI) = 1.21 (1.12–1.30)] and developing diabetes post‐transplant [1.06 (1.02–1.11)]. Donor's history of diabetes was also independently associated with higher mortality [1.10 (1.02–1.19)]. Furthermore, donor's history of diabetes was also associated with an increased the risk of liver graft failure [1.35 (1.24–1.47)]. Conclusions Presence of type 2 diabetes pre‐ and post‐transplant, as well as presence of type 2 diabetes in the donors, are all associated with an increased risk of adverse post‐transplant outcomes.